Effect Of Titanium On Corrosion Behavior Of Aluminum Alloy 3104 As a Candidate Material For Radiator Combustion Engines - Arief Syarifuddin Fitrianto; Bambang Soegijono; Caing Caing; Hamdan Akbar Notonegoro (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2021)
Aluminum Alloy 3104 is aluminum usually used for beverage can. By modifying the content of Titanium content in the alloy, it is expected that this material will be suitable for radiator engine combustion. Especially for its corrosion behavior in coolant solution. Aluminum alloy with different content of Titanium was investigated on its crystal structure, morphology and its corrosion behavior in ethylene glycol solution which is usually used as additive in coolant water. X-ray diffractometer, Electron microscope and potentiodynamic were used to investigate the crystal structure, morphology and corrosion behavior respectively. The results show (002) crystal plane dominate the surface of the sample as the Titanium increase. The (111) and (002) crystal plane are very low compare to (022) crystal plane. Crystallite size and micro strain are affected by addition of Titanium. Surface morphology are clearly affected by the addition of Titanium. Addition of Titanium causes corrosion behavior of the samples. It concludes that the aluminum alloy with different Titanium content in this research, can be used for making radiator combustion engine.